Four new species of Phyllophaga Harris (Coleoptera: Scarabaeidae: Melolonthinae) from western Cuba - Serrano, Annery; Morón, Miguel Ángel (Zootaxa, 2017)
Four new species in the genus Phyllophaga Harris 1827, subgenus Cnemarachis Saylor 1942 (Coleoptera: Scarabaeidae: Melolonthinae) from Cuba are described: Phyllophaga barroi new species, Phyllophaga guanahacabibensis new species, Phyllophaga pauli new species, and Phyllophaga sabanalamarensis new species. Each species is illustrated using photographs of the habitus, diagnostic features, and male aedeagi. A map is provided showing the geographical distributions of the new species.